Zdobnictwo ludowe na Podhalu jako znak (na przykładzie Bukowiny Tatrzańskiej) - Koszarek, Bartłomiej (Zeszyty Wiejskie, 2010)
The phenomenon of Podhale art is still alive and it is constantly evolvingtogether with the inhabitants of this land. It is not the kitsch as some people claim but the real art. Nowadays Bukowina Tatrzańska which iscalledby experts atown of artists, isfamous for handicrafts made of metals and leather. The process of manufacturing was started by Józef Bigos (1890-1966), anoutstand-ing artist from Podhale. Handicraftscooperatives created after the 2nd World War were based on his idea. His heritage is sustained by contemporary artists from Bukowina. The unique character of Bukowina decorative folk is invariably con-nected with the undeniable charm of the Tatra Mountains. The people who grew there are tough and hardened in the fight with the rights of nature, but they are stillsensitive to the surrounding beauty and aware of the fragility of life.